Contralateral effects of eccentric exercise and delayed onset muscle soreness (DOMS) of the plantar flexors: Evidence of central mechanism involved / Suresh Marathamuthu - Suresh , Marathamuthu (2020)
Peripheral and central factors play important roles in the reduction of motor performance following a damaging eccentric exercise and delayed onset of muscle soreness (DOMS). Following this regime, contralateral limb could also be affected, however, the factors involved are inconclusive. The purpose of this study was to distinct contribution of peripheral and central factors following eccentric contraction and DOMS of the plantar flexors in both treated and contralateral homologous limb. Ten males (BMI = 25.08 ± 1.69 kgm-2; age = 28.70 ± 4.24 years) were randomly assigned to experimental (DOM) or control (CON). The DOM group was treated with a damaging eccentric exercise, while CON rested. Plasma creatine kinase concentration (CK), visual analogue scale (VAS), muscle stiffness, maximal voluntary contraction (MVC) and voluntary activation (VA) were measured at pre, post-10 min, -24, -48, -72 hour, on both treated and contralateral limb. After the exercise, CK increased up-to post-48 hour, while VAS up-to post-72 hour compared to pre. Importantly, MVC was reduced at all-time points with greatest drop at post-24 hour (-16%), while VA affected up to post-48 hour with greatest drop at post-10 minute (-7%). Interestingly, a ‘cross-over effect’ was observed in the contralateral limb when VAS, MVC, and VA were negatively affected following the same pattern (time line) as in the treated limb (-13% peak MVC drop; -3.5% peak VA drop). These findings suggest a substantial central contribution to the drop in force especially immediately after the exercise and to a lesser extent the later part of DOMS in both treated and contralateral limb.